Efektivitas Media Promosi Kesehatan Tentang Pengetahuan Tuberculosis Terhadap Pasien Puskesmas Kebonsari Surabaya - Muchamad Alfian Riski Rachmatjaya (Journal of Educational Innovation and Public Health, 2023)
TB is an infectious disease that is easily transmitted caused by the bacterium Mycobacterium tuberculosis. This bacterium can attack several organs in the body but most of these bacteria attack the lungs. The most common transmission is through droplet infection by TB patients. Efforts to convey information on media selection are very important and need to be considered because the correct selection and delivery will provide maximum results in increasing knowledge, attitudes and intentions. This type of research is qualitative research using a qualitative approach. The delivery of learning material at the Kebonsari Health Center uses online, namely like looking through social media. Based on the results of the research and also the results of the interviews conducted by the researchers, it was shown that the delivery of TB material using promotional media, print media, such as leaflets and posters, was effectively used and contributed to rehabilitation patients at the Kebonsari Health Center in Surabaya. Because patients think that the delivery of material uses a new leaflet for them and patients pay more attention to the material presented.